2019
DOI: 10.1038/s41386-019-0579-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal secretion of a psychosis-altered miRNA that regulates glutamate receptor expression is affected by antipsychotics

Abstract: The ability of small secretory microvesicles known as exosomes to influence neuronal and glial function via their microRNA (miRNA) cargo has positioned them as a novel and effective method of cell-to-cell communication. However, little is known about the role of exosome-secreted miRNAs in the regulation of glutamate receptor gene expression and their relevance for schizophrenia (SCZ) and bipolar disorder (BD). Using mature miRNA profiling and quantitative real-time PCR (qRT-PCR) in the orbitofrontal cortex (OF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 75 publications
1
40
1
Order By: Relevance
“…A research revealed that the inhibition of astrocytic miR-223 decreased the exosome mediated reduction in the expression of glutamate Receptor, Ionotropic, N-Methyl D-Aspartate 2B (Grin2b) in neurons. As a result, they found that this psychosis-altered miRNA can regulate the expression of glutamate receptors which are antagonized by antipsychotics (Amoah et al, 2019).…”
Section: Other Diseases and Inflammationmentioning
confidence: 99%
“…A research revealed that the inhibition of astrocytic miR-223 decreased the exosome mediated reduction in the expression of glutamate Receptor, Ionotropic, N-Methyl D-Aspartate 2B (Grin2b) in neurons. As a result, they found that this psychosis-altered miRNA can regulate the expression of glutamate receptors which are antagonized by antipsychotics (Amoah et al, 2019).…”
Section: Other Diseases and Inflammationmentioning
confidence: 99%
“…Such vesicles can traffic aberrantly expressed miRNA between cells, effectively regulating RNA translation in nearby cells. As such, several differentially expressed miRNA have been detected in exosomes in plasma from patients with BD (refer to Table 1), and these vesicles may be useful for isolating miRNA from the periphery for use as biomarkers of diagnosis or treatment response [38,41,42].…”
Section: Micro Rna In Mood Disordersmentioning
confidence: 99%
“…On the contrary, exosomes derived from healthy individuals and peripherally injected into chronically stressed mice had an antidepressant effect 134 . In further support for the role of exosomal miRNAs in the pathophysiology of affective disorders, Amoah et al uncovered an astrocyte-enriched and exosome-secreted miRNA significantly increased in the orbitofrontal cortex (OFC) of BD and schizophrenia patients with a positive history of psychosis at the time of death 135 . This up-regulation correlated with lower expression levels of its targets glutamate ionotropic receptor NMDA-type subunit 2B (GRIN2B) and glutamate ionotropic receptor AMPA-type subunit 2 (GRIA2).…”
Section: Introductionmentioning
confidence: 98%
“… Increases the number of immature neurons and newborn mature neurons in the mouse hippocampal DG. 135 KD knockdown, 5-HTR1A 5-hydroxytryptamine/serotonin receptor 1A, BDNF brain-derived neurotrophic factor, BLA basolateral amygdala, cKO conditional knockout, CRFR1 corticotropin-releasing factor receptor 1, CSF cerebrospinal fluid, PTEN phosphatase and tensin homolog, DCC deleted in colorectal cancer, DG dentate gyrus, DUSP1 dual-specific phosphatase 1, FKBP51 FK506-binding protein 51, FST forced swim test, GABA Îł-aminobutyric acid, GR glucocorticoid receptor, GSK3ÎČ glycogen synthase kinase 3 beta, HDAC4/5 histone deacetylase 4/5, HECTD1 HECT domain E3 ubiquitin protein ligase 1, i.c.v. intracerebroventricular, KD knockdown, Limk1 LIM motif-containing protein kinase 1, miRNA or miR microRNA, mPFC medial prefrontal cortex, NORT novel object recognition test, NSFT novelty-suppressed feeding test, SERT serotonin transporter, SGK1 serum- and glucocorticoid-inducible protein kinase-1, SIRT1 sirtuin 1, SIT social interaction test, mEPSC mini excitatory postsynaptic currents, SPT sucrose preference test, STAT3 signal transducer and activator of transcription 3, TKO triple constitutive knockout, TST tail suspension test, VLO ventrolateral orbital cortex, vmPFC ventromedial prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%